Mirabegron: the review of current knowledge of safety and efficacy in the relief of overactive bladder symptoms - Aleksiewicz, Tomasz; Leis, Kamil; Świerczyński, Wojciech; Miętkiewicz, Kacper; Litwin, Katarzyna; Gałązka, Przemysław (Journal of Education, Health and Sport, 2018)
Mirabegron has been registered as the first strong and selective agonist of the β3 receptor. It is currently used for relief of symptoms of overactive bladder (OAB). That onerous illness involving urgency and detrusor overactivity, that may be accompanied by incontinence, affects approx. 16% of the population. Before registration of Mirabegron, the main pharmacological and non-surgical therapeutic method was the treatment with anti-muscarinic drugs, associated with burdensome adverse effects. Clinical trials on over 10,000 participants demonstrated efficacy and safety of Mirabegron. Besides monotherapy, attempts are being made to use Mirabegron in combined therapy of OAB. The innovative mechanism of action of the drug makes it an attractive option not only in treatment of conditions of the urinary system, but also of metabolic disorders and diseases of the cardiovascular system. This article provides a review of the current knowledge and recent reports regarding Mirabegron - an alternative in treatment of the common and onerous disease of overactive bladder.